A Woodward-Hoffmann approach to the C60 cluster opening leading to homo[60]fullerenes - Kemner, Ewout; Hirsch, Andreas; Zerbetto, Francesco (Journal of Physical Chemistry A, 2004)
The electrocyclic valence isomerization interconverting bismethano[60]fullerenes 1 and 2 with 1,2,3,6(type I) and 1,2,3,4-addition patterns (type II) into the corresponding cluster-opened bismethanohomo[60]fullerenes was investigated computationally with respect to the energy profile and to the retention of molecular orbital symmetry. Whereas for 1 the closed form is unstable and spontaneously isomerizes to the cluster-open adduct, the energy difference between the open and closed isomers of 2 is comparatively small. The B3LYP/6-31G* energy of open 2 is only 1. 2 kcal mol higher than that of the closed form. Analysis of the frontier orbital symmetries of 1,2, and the [5,6]-bridged methano-homo[60]fullerene 3 showed that during these electrocylic valence isomerizations the orbital symmetry is retained and, as a consequence, a Woodward-Hoffmann-type selection principle is valid.